2017
DOI: 10.1556/018.68.2017.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Biological changes of green pea (Pisum sativum L.) by selenium enrichment

Abstract: Supplement of common fertilizers with selenium (Se) for crop production will be an effective way to produce selenium-rich food and feed. The value of green pea seeds and forages as alternative protein source can be improved by using agronomic biofortification. Therefore, biological changes of green pea (Pisum sativum L.) and influences of inorganic forms of Se (sodium selenite and sodium selenate) at different concentrations on the accumulation of magnesium (Mg) and phosphorus (P) were investigated in greenhou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Foliar application of Se at late growth stages seems to optimize the uptake, translocation, and distribution of Se into the edible portions of plants, whereas selenate is more efficiently accumulated in plant tissues than selenite [100]. The tolerable Se content in most plant species is between 10 and 100 mg kg −1 DW [101] and phytotoxic effects due to Se excess can compromise plant growth through damages to photosynthetic apparatus, photosynthesis inhibition, and over-production of starch [102]. In addition, secondary accumulators, also called Se-indicator, as some vegetables of the Asteraceae, Brassicaceae, and Fabaceae family, when supplied with exogenous Se can accumulate up to 1 g kg −1 DW, being a good target for Se biofortification [101].…”
Section: Seleniummentioning
confidence: 99%
“…Foliar application of Se at late growth stages seems to optimize the uptake, translocation, and distribution of Se into the edible portions of plants, whereas selenate is more efficiently accumulated in plant tissues than selenite [100]. The tolerable Se content in most plant species is between 10 and 100 mg kg −1 DW [101] and phytotoxic effects due to Se excess can compromise plant growth through damages to photosynthetic apparatus, photosynthesis inhibition, and over-production of starch [102]. In addition, secondary accumulators, also called Se-indicator, as some vegetables of the Asteraceae, Brassicaceae, and Fabaceae family, when supplied with exogenous Se can accumulate up to 1 g kg −1 DW, being a good target for Se biofortification [101].…”
Section: Seleniummentioning
confidence: 99%
“…However, higher doses of both selenite and selanate had the opposite effect. Similarly, Garousi et al [2017] observed that when selenite was applied to peas at a dose exceeding 30 mg•kg -1 , the maximum photochemical efficiency of PSII (F v /F m ) decreased. Ghasemi et al [2016] sprayed a broccoli plantation with sodium selenate at doses ranging from 10 to 100 μg Se ml -1 and found that selenium did not affect chlorophyll fluorescence parameters such as F 0 , F v /F m , and Y.…”
Section: Discussionmentioning
confidence: 81%
“…They are assimilated into various Se metabolites in the cells of vegetables (Figure 2). Vegetables, such as turnip (Li et al, 2018a), lettuce (Hawrylak-Nowak, 2013), and green pea (Garousi et al, 2017), accumulate more Se contents by supplying selenate as compared with selenite.…”
Section: Se Sourcementioning
confidence: 99%